A Sár Mesterei - Vargyasi, Levente (Romania, 2011)
In the Transylvanian town of Nagyborosnyó, a large percentage of the gypsy population still earns its livelihood through brick-making. This film provides insight into the long-standing tradition of brick-making, and into the everyday life of the Romanian brick-makers who live there.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films